Influence Analysis in Social Networks: Examining Safety and Privacy Risk Levels of the High School Students to Personality Measures - Uğur Bakan (Selçuk İletişim)
The sexual abuse of children or any sexual contact with them by an adult or older adolescent is not a new phenomenon. Sexual assault does not always involve physical contact – acts such as voyeurism and exhibitionism yet it can be regarded as unwanted sexual attention. Sexual assault is arguably one of the few crimes for which high school students are at greater risk than the general population. With the widespread use of the Internet forming a global network, a heterogeneous social network that allows interaction between individuals and communities residing in different regions has been created. Social media provides many possibilities for researchers as an area in which information, views, and interests representing people's identities are shared through virtual communication. The purpose of this study was to determine specifically how to protect high school students from sexual assaults and awareness of privacy. This paper is expected to shed light on a relatively similar subject, however, in a whole new environment that emerged along with the digital era. This study is a descriptive one and it was figured with survey method. The test is to be taken within a 45-minute period. This scale is used in the virtual environment to determine the attitudes of the individuals and the cognitive factors affecting the media choice of the individual. Total 600 students (Male=293, Female=307) answered an online questionnaire during the May 2016. Our findings point to the complex ways in which young people use social media, identity and the sexual assault risk on SNSs.